Competing mechanisms in the wear resistance behavior of biomineralized rod-like microstructures. (November 2016) - Escobar de Obaldia, Enrique; Herrera, Steven; Grunenfelder, Lessa Kay; Kisailus, David; Zavattieri, Pablo
Abstract: The remarkable mechanical properties observed in biological composite materials relative to those of their individual constituents distinguish them from common engineering materials. Some naturally occurring high-performance ceramics, like the external veneer of the Chiton ( Cryptochiton stelleri ) tooth, have been shown to have superior hardness and impressive abrasion resistance properties. The mechanical performance of the chiton tooth has been attributed to a hierarchical arrangement of nanostructured magnetite rods surrounded with organic material. While nanoindentation tests provide useful information about the overall performance of this biological composite, understanding the key microstructural features and energy dissipation mechanisms at small scales remains a challenging task. We present a combined experimental/numerical approach to elucidate the role of material deformation in the rods, debonding at the rod interfaces and the influence of energy dissipation mechanisms on the ability of the microstructure to distribute damage under extreme loading conditions. We employ a 3D finite element-based micromechanical model to simulate the nanoindentation tests performed in geological magnetite and cross-sections of the chiton tooth. This proposed model is capable of capturing the inelastic deformation of the rods and the failure of their interfaces, while damage, fracture and fragmentation of the mineralized rods is assessed using a probabilistic function. Our results show that these natural materials achieve their abrasion resistant properties by controlling the interface strength between rods, alleviating the tensile stress on the rods near the indentation tip and therefore decreasing the probability of catastrophic failure without significantly sacrificing resistance to penetration. The understanding of these competing energy dissipating mechanisms provides a path to the prediction of new combination of materials. In turns, these results suggest certain guidelines for abrasion resistance rod-like microstructures in composites with high volume fraction of brittle minerals or ceramics with tailored performance for specific applications. Graphical abstract: Highlights: We study a tough and abrasion resistant naturally-occurring biological composite. These material have a rod-like microstructure with 90% magnetite rods and α-chitin. We employ indentation data and computational models to understand energy dissipation. Rods inelastic deformation, brittle failure and interfaces debonding are analyzed. We devise design guidelines based on these competing mechanisms.